Fluoride bioavailability on demineralized enamel by commercial mouth rinses - Valdivia-Tapia,Astrid Carolina (2021)
Abstract The ability of mouth rinses, available in the international market, to form reaction products on demineralized enamel (bioavailability test) was evaluated in vitro. Nine mouth rinses purchased in Chile were evaluated; eight formulated with NaF (one containing 100 µg F/mL and seven containing 226) and one with Na2FPO3 (226 µg F/mL as ion F). Demineralized enamel slabs (n=15 per mouth rinse) were sectioned; one half was subjected to the assigned mouth rinse treatment for 10 min and the other half was used to obtain baseline data. Loosely bound and firmly bound fluoride formed on enamel were determined with an ion-specific electrode and the values were expressed in µg F/cm2. The concentration of fluoride and the pH of the mouth rinses were previously determined. Concentrations of loosely bound and firmly bound fluoride formed on enamel were independently analyzed by ANOVA and Tukey’s test (α=5%). The loosely bound and firmly bound fluoride concentrations (µg F/cm2) formed ranged from 3.2 to 36.2 and 0.4 to 1.7, respectively. Loosely bound fluoride formed on enamel was significantly more effective in discriminating the effect of different commercial mouth rinses than firmly bound fluoride. Mouth rinses with 226 ppm F as NaF and low pH presented significantly greater bioavailability of fluoride on enamel than those with higher pH or lower NaF concentration. The mouth rinse with Na2FPO3 showed low reactivity. Although further studies are necessary, the findings showed that commercial fluoride-containing mouth rinses have important variations in enamel fluoride bioavailability, which may result in differences on anticaries efficacy.